Implementasi Algoritma Crochemore-Perrin Pada Aplikasi Silsilah Keturunan Nabi Berbasis Android - Afrinda Yunus Siregar (Journal of Information System Research (JOSH), 2020)
The prophet who is obliged to believe there are only twenty-five (25) prophets, in the twenty-five prophets, every prophet has a genealogy, with so many genealogies of the Prophet, every Muslim, especially young men and women, need to know the genealogy of the Prophet , it would be a problem if when someone asked about the Prophet's lineage did not know at all, because many Muslims curiosity about the Prophet's genealogy was few and only certain people knew. In the case of searching the genealogy of the Prophet, the Crochemore-Perrin algorithm is very suitable to use because it is able to search from two directions, from front and back, the Crochemore-Perrin algorithm factifies the pattern into two parts of the left pattern, and the right pattern so that the pattern is the same as the left pattern. right. Crochemore-Perrin algorithm can solve the problem of searching the Prophet's lineage because it is easier and faster. The solution to the problem of these problems is to design and build a search application for the Prophet's genealogy that is easily accessible wherever it is and easy to operate. With the application of the genealogy of prophets is expected to facilitate the Islamic community to find and know about the genealogy of the Prophet